Antioxidant treatment normalizes mitochondrial energetics and myocardial insulin sensitivity independently of changes in systemic metabolic homeostasis in a mouse model of the metabolic syndrome. (August 2015) - Ilkun, Olesya; Wilde, Nicole; Tuinei, Joseph; Pires, Karla M.P.; Zhu, Yi; Bugger, Heiko; Soto, Jamie; Wayment, Benjamin; Olsen, Curtis; Litwin, Sheldon E.; Abel, E. Dale
Abstract: Cardiac dysfunction in obesity is associated with mitochondrial dysfunction, oxidative stress and altered insulin sensitivity. Whether oxidative stress directly contributes to myocardial insulin resistance remains to be determined. This study tested the hypothesis that ROS scavenging will improve mitochondrial function and insulin sensitivity in the hearts of rodent models with varying degrees of insulin resistance and hyperglycemia. The catalytic antioxidant MnTBAP was administered to the uncoupling protein-diphtheria toxin A (UCP-DTA) mouse model of insulin resistance (IR) and obesity, at early and late time points in the evolution of IR, and to db/db mice with severe obesity and type-two diabetes. Mitochondrial function was measured in saponin-permeabilized cardiac fibers. Aconitase activity and hydrogen peroxide emission were measured in isolated mitochondria. Insulin-stimulated glucose oxidation, glycolysis and fatty acid oxidation rates were measured in isolated working hearts, and 2-deoxyglucose uptake was measured in isolated cardiomyocytes. Four weeks of MnTBAP attenuated glucose intolerance in 13-week-old UCP-DTA mice but was without effect in 24-week-old UCP-DTA mice and in db/db mice. Despite the absence of improvement in the systemic metabolic milieu, MnTBAP reversed cardiac mitochondrial oxidative stress and improved mitochondrial bioenergetics by increasing ATP generation and reducing mitochondrial uncoupling in all models. MnTBAP also improved myocardial insulin mediated glucose metabolism in 13 and 24-week-old UCP-DTA mice. Pharmacological ROS scavenging improves myocardial energy metabolism and insulin responsiveness in obesity and type 2 diabetes via direct effects that might be independent of changes in systemic metabolism. Highlights: Obesity impairs mitochondrial energetics and increases mitochondrial ROS in the heart. These changes are associated with decreased insulin-mediated glucose utilization. Treatment with a targeted antioxidant MnTBAP restores mitochondrial function and prevents ROS overproduction. Antioxidant treatment normalizes myocardial insulin responsiveness. These changes are independent of changes in systemic metabolic homeostasis.